Islamic Economic Education Policy in Higher Education for Forming Islamic Financial Human Resources in Indonesia - Maolani, Dedeng Yusuf (International Journal of Psychosocial Rehabilitation, 2020)
The main problem in this research is the rapid development of the Islamic economy in Indonesia, not accompanied by the availability of Human Resources (HR), both in quality and quantity, to meet the needs of the Islamic economic and financial industry. The purpose of this study is to determine the Islamic economic education policy that is applied in Higher Education in preparing the human resources needed by the Islamic economic and financial industry in Indonesia. Researchers used the documentation and literature study method which is closely related to Islamic economic education policy and other references in the form of previous research results, regulations, policies, and theories from various textbooks. The results of this study found that from an institutional standpoint, sharia economic education policies at tertiary institutions in Indonesia used a variety of nomenclature. So we need a policy on structuring educational nomenclature in the field of sharia economics in tertiary institutions. From the curriculum side, researchers also found the same problem. Until now there has been no policy at the national level in terms of standardization of the national Islamic core economic curriculum. So there needs to be a core curriculum policy agreed upon by the elements of higher education and professional associations that are competent in the field of sharia economics to agree on a number of courses that must be given to produce the main competencies of graduates required by the Islamic finance industry.